2017
DOI: 10.3389/fimmu.2016.00670
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Marginal Zone B-Cell Differentiation by MicroRNA-146a

Abstract: B-cell development in the bone marrow is followed by specification into functional subsets in the spleen, including marginal zone (MZ) B-cells. MZ B-cells are classically characterized by T-independent antigenic responses and require the elaboration of distinct gene expression programs for development. Given their role in gene regulation, it is not surprising that microRNAs are important factors in B-cell development. Recent work demonstrated that deficiency of the NFκB feedback regulator, miR-146a, led to a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
(57 reference statements)
2
24
0
Order By: Relevance
“…Notch signaling has been found to be directly affected by miR-146a in many tissues [ 62 , 63 , 64 ]. Our transcriptomics and proteomics data confirmed by western blot analysis, along with in silico analysis of miR-146a-predicted targets with the presence of miR-146a binding site in Notch-2- and Numb 3′-UTRs [ 45 ], suggest that both Numb and Notch-2 are novel targets of miR-146a in human primary LECs and organ-cultured corneas ( Supplementary Tables S1 and S2 , Figure 5 and Figure 6 ). Overexpression of miR-146a induced repression of Numb and an increase in Notch-1 expression level, which is in agreement with earlier verified miR-146a direct target studies [ 63 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Notch signaling has been found to be directly affected by miR-146a in many tissues [ 62 , 63 , 64 ]. Our transcriptomics and proteomics data confirmed by western blot analysis, along with in silico analysis of miR-146a-predicted targets with the presence of miR-146a binding site in Notch-2- and Numb 3′-UTRs [ 45 ], suggest that both Numb and Notch-2 are novel targets of miR-146a in human primary LECs and organ-cultured corneas ( Supplementary Tables S1 and S2 , Figure 5 and Figure 6 ). Overexpression of miR-146a induced repression of Numb and an increase in Notch-1 expression level, which is in agreement with earlier verified miR-146a direct target studies [ 63 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 57%
“…miR-146a is an important regulator of many cellular functions and targets different genes in different cell types [ 40 , 41 , 42 ]. It plays a major role in several diseases, such as diabetes [ 40 ], cancer [ 41 ], and Graves ophthalmopathy [ 42 ], and its association with different pathways suggests its involvement in cell migration [ 9 , 10 , 43 ], invasion [ 44 ], differentiation [ 45 ], and proliferation [ 44 ]. Our previous studies also revealed that miR-146a plays a regulatory role in corneal wound healing and limbal epithelial stem cell maintenance in normal and diabetic corneas [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marginal zone B cells and FOB exhibit different gene expression profiles ( 18 , 19 ), which contribute to their differential localization and function. MZB have an IgM high IgD low CD21 high CD23 − CD1d high phenotype ( 20 ), which is distinct from FOB that are IgM low IgD high CD21 low CD23 high CD1d − .…”
Section: Introductionmentioning
confidence: 99%
“…For example, King et al [46] reported that miR-146 is an important regulator of Notch2 signaling which influences the development of marginal-zone (MZ) B cells by targeting the Numb gene. Furthermore, miR-205 can maintain T cell development by regulating Forkhead box N1 (FOXN1), in the condition of a changed thymic microenvironment induced by stress such as infections, radiation exposure, and steroids [47].…”
Section: Discussionmentioning
confidence: 99%